Insights into management and physiological determinants of lowest pod height in soybean - Goufo, Piebiep; Kluver, Robert; Cerrudo, Aníbal Alejandro; Naeve, Seth (Wiley, 2024)
Harvest losses caused by the low height of the lowest pods (LPH) are a significant issue in soybean cultivation. Minimizing these losses requires identifying management, physiological, and agronomic factors that interactively modulate LPH. Four studies were conducted to examine the relationships among soybean LPH, node and internode features, and light quality under different management practices. These practices included population density (19, 31, and 43 plants m−2) and row width (equidistant, 25, 51, and 76 cm), relative maturity (maturity group [MG] 0.8, MG 2.1, and MG 2.8), mulch color (gray bare soil, red mulch, and white mulch), and timing of stand reduction (V1, R3, R4, and R5 growth stages). An increase in population density from 19 to 43 plants m−2 led to an average increase in LPH of 28%, from 11.9 to 15.3 cm. LPH was not influenced by row width. Later maturing cultivars demonstrated the highest potential for enhancing LPH, with late AG2802 having a higher LPH (18.8 cm) than early AG0803 (12.4 cm). Data indicated that the elongation of internodes 10, 11, and 12, along with changes in the red to far-red light ratio beneath the canopy, plays a pivotal role in determining the location of the lowest pods. Moreover, LPH is established around the R3 growth stage. Nevertheless, further investigations are warranted to gain a better understanding of how these parameters, individually and collectively, influence LPH in soybean.